The Applicability of Linguistic Politeness Studies to Translation: A Case Study - Rosa Lorés Sanz (Miscelánea: A Journal of English and American Studies, 1998)
The present paper picks up on some aspects of a complex attempt to approach politeness studies from a new angle: translation. The most relevant approaches to the study of politeness agree on its two-sided character, which entails, on the one hand, linguistic meaning and, on the other, social meaning. This twofold concept of politeness determines the close relationship between its linguistic expression and the cultural context within which such expression is used. The cultural-relativistic stand that this assumption implies in some ways contradicts or, at least, partly questions, the universal character ascribed to linguistic politeness by one of the seminal - theories in the field: the framework of Politeness theory devised by Penelope Brown and Stephen Levinson in their book Politeness: Some Universals in Language Usage (1978, 1987). In my view, politeness theory and the discussion about what is universal and what is culturally-determined in politeness can benefit from contrastive studies in the field of translation, and translation can also profit from insights into the study of linguistic politeness, as it is my intention to illustrate here with Cat on a Hot Tin Roof and La gata sobre el tejado de zinc caliente as corpora.